Response of mlallchilng on in sihd soil moisture, grow&%yai,e ld and ecrolnomic return of litchi (Litchi chinensis) nnder rainfed cornadition in Mpnra* - PRAKASH, JAI; S1NGH, N P; SANKARAN, M (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2003-05 to improve the productivity of orchard and fertility of soil on 10-year-old bearing trees of 'Bombai' litchi (Litchi chinensis SOM.). The investigation was carried out with 4 treatments, viz unmulched (control), plastic mulch (black polythene sheets), Gliricidia green leaves and chhan mulch with 4 replications under a randomized block design. The effects of mulches were significantly recorded on growth of trees, fruit cracking and fruit yield. The fruit yield in Gliricidia mulch was 2.865 tonneska, followed by 1.995 tonneska under chhan mulch, whereas the lowest fruit yield (1.613 tonneska) was noticed under unmulched trees. However, the Gliricidia mulching was significantly effective on tree height, canopy, and shoot growth, fruit cracking and yields of fruits as compared to other mulches and control. The in-situ soil moisture status also increased during summer and winter season under different mulches in comparison to control. The higher per cent of soil moisture increase was recorded under Gliricidia green leaves over the other treatments. The benefit:cost ratio was also higher under various mulching over control. It can be concluded that the mulching is a beneficial practice for higher income from litchi orchards of tilla land of Tripura under rainfed condition.